2022
DOI: 10.21203/rs.3.rs-1609845/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 Vaccination on the Menstrual Cycle: A Cross-Sectional Study from Karachi, Pakistan

Abstract: Background The COVID-19 disease triggered a worldwide health catastrophe. To deal with this deadly situation multiple vaccines were developed and a mass immunization program started globally. However, vaccine hesitancy was seen especially among women of reproductive age, having concerns that the vaccine might affect their menstrual cycle. This study investigated the link between COVID vaccination and menstrual abnormalities. It is essential for us to understand the effects of vaccines on menstruation as menstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There was a significant relation between the COVID 19 vaccination and menstrual irregularity in the reproductive age group (p value 0.02) with median age group 30 years. In the study, Suaeleh et al [7] , showed median age group of 21 years and majority of participants had normal BMI. MM Al-Mehaisen et al [8] , analyzed the menstrual flow and observed statistically significant change in the flow with 24.5% of participants had increased flow and 15.5% had reduced flow.…”
Section: Discussionmentioning
confidence: 90%
“…There was a significant relation between the COVID 19 vaccination and menstrual irregularity in the reproductive age group (p value 0.02) with median age group 30 years. In the study, Suaeleh et al [7] , showed median age group of 21 years and majority of participants had normal BMI. MM Al-Mehaisen et al [8] , analyzed the menstrual flow and observed statistically significant change in the flow with 24.5% of participants had increased flow and 15.5% had reduced flow.…”
Section: Discussionmentioning
confidence: 90%